PENGARUH PENGGUNAAN LARUTAN KUMUR EKSTRAK BUAH NANAS (Ananas comosus L. Merr) TERHADAP PENURUNAN JUMLAH KOLONI BAKTERI PLAK PENDERITA GINGIVITIS RINGAN - Feby Resicha; Andani Eka Putra; Kosno Suprianto (Andalas Dental Journal, 2016)
Dental plaque is the main cause of gingivitis. Plaque control mechanically or chemically is an effort to prevent and eliminate dental plaque. Chemical control is done by mouthwash. Pineapple extract contains bromelain enzyme which has antibacterial feature. To find the effect of using pineapple-extracted mouthwash in reducing bacterial colonies in dental plaque of mild gingivitis patients. This study was experimental laboratoris using pre- test and post-test with control group design, conducted in January-February 2018. Sample was 20 female students living in dormitory of Andalas university, divided into two group of treatment (using 50 % pineapple- extracted mouthwash) and control (using aquadest). Data was analyzed by T-test using SPSS. The result showed average drop of bacterial colonies in dental plaque of treatment group was higher than control group. Independent T-test showed that there was significant difference of bacterial colonies count between two groups (p=0.00). This was influenced by bromelain which has antibacterial feature by reducing bacterial surface tension with hidrolizing protein and glycoprotein in saliva that become the mediator of bacteria to adhere in dental surface. Mouthwash using 50 % pineapple-extracted solution for four days was proven to reduce bacterial colonies in dental plaque of mild gingivitis patients.